Composite DOBC with fuzzy fault‐tolerant control for stochastic systems with unknown nonlinear dynamics. (23rd October 2019) - Sun, Shixiang; Ren, Tao; Wei, Xinjiang
Summary: A class of stochastic nonlinear systems with fault and multisource disturbances is concerned. The fault is a general bounded actuator fault, and the multiple disturbances include partial‐known information disturbance and white noise. A stochastic adaptive disturbance observer is constructed to estimate the partial‐known information disturbance, based on which the partial‐known information disturbance can be compensated in the feed‐foreword channel immediately. Also, the multiplicative white noise can be attenuated by the designed feedback controller. To make the composite system is satisfactory, a composite disturbance based‐observer control with fuzzy fault‐tolerant control is proposed. The pole placement and LMI method is applied to attenuate and reject the disturbance. Furthermore, the fault can be compensated simultaneously. To verify the feasibility and availability of the designed control scheme, a simulation example is shown finally.